UJI DAYA ANTIBAKTERI EKSTRAK DAUN KETAPANG (Terminalia catappa L) TERHADAP PERTUMBUHAN BAKTERI Vibrio harveyi SECARA IN VITRO - Aulia, Deni; Indrayati, Artin; Jarir, Dewi Virgiastuti; Hadiwinata, Bagus; Suprakto, Bambang; Sabariyah, Nunung; Wartini, Sri (Jurnal Perikanan Unram, 2024)
Vibrio harveyi is a bacterial disease that is commonly found in aquaculture activities. Antibiotics used in aquaculture to prevent and treat the disease outbreak cause adverse effects. Ketapang leaves (Terminalia catappa L) are known to contain chemical compounds such as flavonoids, alkaloids, phenolics, tannins, and saponins that can act as antibacterial. This study aims to determine the antibacterial inhibitory of Ketapang leaf extract against Vibrio harveyi. The inhibitory test was carried out with 5 types of treatments, including 1 treatment without Ketapang leaves (control) and 4 treatments of Ketapang leaves with different concentrations; 15, 30, 60, and 120 grams of Ketapang leaves/liter. Each treatment consists of 3 replications. Ketapang leaf extract showed antibacterial inhibitory against Vibrio harveyi with mean resistance value of each concentration (Mean ± SEM); 7.53 ± 0.13 mm (15 grams/liter); 7.70 ± 0.36 (30 grams/liter); 8.25 ± 0.15 (60 grams/liter); and 9.62 ± 0.83 (120 grams/liter). Ketapang leafless treatment (control) showed no antibacterial inhibition. Ketapang leaf extract showed antibacterial inhibition against Vibrio harveyii with comparable inhibitory against extract concentration.